The encyclopedia of war movies : the authoritative guide to movies about wars of the twentieth century - Davenport, Robert Ralsey, 1950- (New York, NY : Facts On File, 2004)
Presents an overview of more than eight hundred films featuring armed conflicts, including "All Quiet on the Western Front," "The Great Escape," "The Thin Red Line," and "Schindler's List."
Includes bibliographical references (p. 405-407) and index.
Keywords: War films -- Catalogs